The Effect of Bulbs Size and the Type Fertilizer in the growth of Lilium Longiflorum and its Flowerin (Journal of Hama University, 2020)
The study was conducted to explore the effect of the type of fertilizer and the size of the bulbs grown on the growth and flowering of the Lilium Longiflorum under the conditions of the city of Hama. The experiment was designed according to the dissimilar sectors, the main factor is the quality of the fertilizer (5) (sheepskin manuare, poultry manure, Metallic balanced, Metallic high phosphorus, (Without fertilization), and the dissociating agent size of the bulbs and their number / 2 / Large holes have circumference (21-25 cm), and small cones have circumference (17-20 cm).The following shows:1 - The Lilium Longiflorum  plants responded to the high phosphorus fertilization, which resulted in a significant increase in both vegetative growth indices (number of leaves, leaf length), flowering indices (floral stem length, number of flower buds2 - Although the treatment of fertilization of sheepskin manuare in the vegetative growth indices did not exceed, but it has achieved a significant increase in the indicators of flowering (proportion of the formation of the floral stem, the length of the floral stem), while significantly reduced the number of floral buds compared with the treatment of high mineral fertilization Phosphorus.3. . The treatment of the use of large bulbs (21-25 cm) was significantly superior to the treatment of the use of small bulbs (17-20 cm) in all vegetative growth and flowering indicators except for the number of flower buds4- The combined effect of the large size of the bulb used in agriculture and the high phosphorus mineral fertilizer showed a significant increase in all the studied indicators